The Influence of Board of Directors Personal Characteristics On the Work Performance of Sharia Bank: The Sharia Supervisory Board's Function as a Moderating Variable - Indarti Andarini; Salamah Wahyuni (Cita Konsultindo Research Center, 2023)
The purpose of this study is to provide empirical evidence about the effect of size, educational background, and board independence on the performance of Sharia bank, as well as the role of the Sharia supervisory board in moderating the effect of size, educational background, and board independence on Sharia bank performance. From 2015 through 2021, the sample for this study is Sharia commercial banks and Sharia business units. Purposive sampling is used in the corporate sampling methodology. According to the findings of this study, the size and independence of the board of directors have a favorable and significant impact on the performance of Sharia bank, however educational background has no impact on the performance of Sharia bank. The Sharia supervisory board is proven to moderate the influence of size, educational background, and independence of the board of directors on the performance of Sharia bank.